Usage of soda-soda semi-finished products from rape in cardboard composition - Черьопкіна, Романія Іванівна; Паньковець, Сергій Миколайович (Technology audit and production reserves, 2015)
This article deals with obtaining and using fibrous semi-finished products from annual plants and some results of our research in this area are given. The main aim of the study is the use of clean soda-soda process for broken rape delignification for obtaining fiber semi-finished products to using them in the cardboard manufacture. An influence of the main technological parameters is shown in the article: active alkali charge, addition of NaOH to soda solution, cooking duration, infiltration and presence of anthraquinone catalyst on quality parameters obtained fiber semi-finished products and container cardboard. The proposed technological parameters of soda-soda cooking of broken rape allow to delignificate them to obtain semi-chemical pulp and high yield pulp. It is established the feasibility of using rape fiber semi-finished products for KT-25 and KT-50 container cardboard brands. The research results can be considered as an alternative to waste paper for the cardboard production.